Investigation of seaport air dustiness and dust spread - Baltrėnas, Pranas; Fröhner, Klaus-Diter; Pranskevičius, Mantas (Journal of Environmental Engineering and Landscape Management, 2007)
In the present study investigation of dustiness, performed at Public Limited Liability Company KLASCO, the Company of State Seaport of Klaipeda is described. During investigation the sources of dust formation and the main reasons, impacting the concentration of dust were analysed. Tests were performed at 12 points, located in two zones in the territory of the enterprise. Tests were also performed at the Terminal of Powdery Manure Discharge. Concentrations of dust of manure of potassium chloride during loading were measured. In order to evaluate impact of the enterprise, the data of measurements made at the same time in the northern part of Klaipeda city were used. The obtained data were demonstrated by Surfer 6 software. According to the isolines, analysis of dust spread was performed. Oro dulkėtumo ir dulkių sklaidos tyrimas jūrų uostamiestyje Santrauka. Aprašomi dulketumo tyrimai, atlikti Klaipedos valstybinio jūru uosto kompanijoje AB KLASCO. Analizuojami dulkiu susidarymo šaltiniai ir pagrindines priežastys, turejusios itakos dulkiu koncentracijai. Tyrimai atlikti 12 tašku, išdestytu dviejose zonose imones teritorijoje. Atlikti tyrimai Biriuju trašu krovos terminale. Jame nustatytas kalio chlorido trašu dulkiu koncentracijos krovimo metu. Teršimo poveikiui ivertinti buvo naudoti tuo pat metu atlikti Klaipedos šiaurines miesto dalies duomenys. Gauti duomenys pavaizduoti Surfer 6 programa. Pagal sumodeliuotas izolinijas atlikta dulkiu sklaidos analize. Reikšminiai žodžiai: optinis metodas, svorinis metodas, Biriųjų trašų krovos terminalas, oro dulkėtumas, modeliavimas. Исследование запыленности воздуха и распространение пыли в морском порту Резюме. Исследована запыленность воздуха в морском порту города Клайпеды (компании AO , KLASCO”). Проанализированы источники пыли, а также основные причины, обуславливающие концентрацию пыли. Исследования проведены в 12 местах морского порта, а также в терминале по разгрузке сыпучих удобрений. В нем проведены исследования концентраций хлорида калия. Выявлено влияние загрязненности пылью, использованы данные исследований северной части города Клайпеды. Полученные данные обработаны с помощью программы SURFER 6 и представлены в виде изолиний. Сделан анализ распространения пыли. Ключевые слова: оптический метод, гравиметрический метод, терминал по разгрузке сыпучих удобрений, запыленность воздуха, распространение пыли, моделирование. First Published Online: 14 Oct 2010